Impact of Official Development Assistance on Economic Growth in the East African Community - Litali, Victoria; Opuodho, Gordon; Fatoki, Olanrewaju (European Scientific Journal, ESJ, 2025)
This research focuses on the effect of Official Development Assistance (ODA) on the economic development of the East African Community, with Trade openness as a moderating variable. This study adopts a Vector Error Correction Model (VECM) for 1974-2022 to investigate the cointegration between ODA balance, trade openness, and economic growth in five East African countries. The findings reveal a complex dynamic relationship: whereas ODA has a positive individual impact on economic growth, as well as the interaction of ODA and Trade openness also has a positive and significant effect. This indicates that the characteristics of trade policy condition the ability of ODA to promote economic growth. This means that characteristics of the trade policy condition the ability of ODA to promote economic growth. Based on the findings, the study adds to the ever-ongoing aid inefficiency discourse by underlining the necessity of an ’enabling environment’ in the form of trade openness, significantly boosting the growth impact of ODA. These outcomes have significant implications for policymakers in countries of the third world where compliance with ODA missions could be made efficient by implementing the missions of trade openness. According to the study, there is a call for the strategies of foreign aid and trade liberalization toward the development of economic growth in developing countries.